Spermatogenesis and spermatozoa ultrastructure of two Dipolydora species (Annelida: Spionidae) from the Sea of Japan. (February 2015) - Radashevsky, Vasily I.; Yurchenko, Olga V.; Tyurin, Sergey A.; Alexandrova, Yana N.
Highlights: We describe spermatogenesis and the structure of the spermatozoa of two polychaetes. Spermatids are joined in tetrads in D. bidentata and octads in D. carunculata . We recognize three stages of spermiogenesis according to condensation of chromatin. Polydorin spermatozoa have similar composition but slightly different dimensions. The exact places where fertilization occurs in brooding spionids remain unknown. Abstract: Spermatogenesis and the structure of the spermatozoa of two spionid polychaetes Dipolydora bidentata and Dipolydora carunculata are described by light and transmission electron microscopy. Both species are gonochoristic borers in shells of various molluscs. Proliferation of spermatogonia occurs in paired testes regularly arranged in fertile segments, and the rest of spermatogenesis occurs in the coelomic cavity. Early spermatogenesis occurs quite similarly in the two species but results in formation of tetrads of interconnected spermatids in D. bidentata and octads of spermatids in D. carunculata . Three consecutive stages of spermiogenesis are recognized according to the condensation of chromatin in nucleus: (1) early spermatids with heterogeneous, partly clumped chromatin, (2) middle spermatids with homogeneous, coarsely granular chromatin, and (3) late spermatids with homogeneous fibrillar chromatin. Moreover, late stage of spermatids is further classified into two stages, I and II, according to the position of the acrosome and shape of the nucleus. In late spermatids I, the acrosome is situated in the anterior invagination of the funnel-shaped to oval nucleus, whereas in late spermatids II the acrosome is situated on top of the elongated nucleus. Ultrastructural composition of cells at each stage of spermatogenesis is described and illustrated. The possible process of morphogenesis of organelles during spermato- and spermiogenesis is reconstructed for both species. The proacrosomal vesicle first appears in early spermatids near the Golgi complex and then migrates anteriorly; in the middle spermatids, the acrosome comes to lie in a deep anterior nuclear fossa. In late spermatids I, this fossa evaginates and a posterior fossa develops in the nucleus housing basal body and the anterior part of the axoneme. In late spermatids II, the mitochondria elongate and probably reduce in number due to fusion of some of them. The mature spermatozoa in both species are introsperm with the conical acrosome, subacrosomal plate, long nucleus with short posterior fossa, long midpiece with elongated mitochondria, and long flagellum with 9 × 2 + 2 organization of microtubules. Numerous flat rounded platelets with putative glycogen are present throughout most part of the nucleus and the midpiece. The process of spermatogenesis in D. bidentata and D. carunculata is similar to that in other Dipolydora, Polydora and Pseudopolydora species. Spermatozoa in these polydorin spionids have similar composition and differ mainly in size of the nucleus and the midpiece. Elongated spermatozoa are adapted for transfer in spermatophores and an internal fertilization which is characteristic for brooding species. Diversely modified spermatozoa among spionids may be signs of the diversity of fertilization biology within the Spionidae. The exact places where fertilization occurs in brooding spionids however remains unknown.